1992
DOI: 10.1007/bf00161238
|View full text |Cite
|
Sign up to set email alerts
|

Central retinal vein occlusion in young people

Abstract: In a study performed on 20 subjects with central retinal vein occlusion (CRVO) aged 40 years or less we found the ischemic form in 20%. Disc edema was a common finding at the onset, while macular edema was less frequently seen. Systemic or ocular disorders that could be related with the development of the CRVO were often found; a patient was affected with myasthenia gravis and another with Sturge-Weber syndrome: these two diseases were not previously reported in association with CRVO. In only two of the 11 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 16 publications
0
17
1
Order By: Relevance
“…Conversion rates of 12.6% reported in other studies ranged from 0 [60] to 27% [61] during a follow-up varying from 10 weeks to 13 months after CRVO. The CVOS [55] reported that in the first 4 months of follow-up, 81 (15%) of 547 eyes with good perfusion converted to ischemia.…”
Section: Natural History Of Rvomentioning
confidence: 95%
“…Conversion rates of 12.6% reported in other studies ranged from 0 [60] to 27% [61] during a follow-up varying from 10 weeks to 13 months after CRVO. The CVOS [55] reported that in the first 4 months of follow-up, 81 (15%) of 547 eyes with good perfusion converted to ischemia.…”
Section: Natural History Of Rvomentioning
confidence: 95%
“…Free gas bubbles associated with both Clostridia sp and Bacillus cereus panophthalmitis have been reported, but such cases involved extensive inflammation with necrosis throughout the globe. [1][2][3] In this case there was no evidence of vitritis and the bubbles were present within 1 h of injury, and it is therefore likely that the presence of the bubbles was Figure 2 The metallic foreign body recovered from the patient.…”
Section: Commentmentioning
confidence: 83%
“…Fong et al [ 235 ] in a retrospective study of 103 cases of CRVO in young, nondiabetic adults, followed for at least 6 months, found that 32 % had a fi nal visual acuity of 20/200 or worse and 6 % no light perception. Giuffré et al [ 236 ], in a study of 20 patients with CRVO aged 40 years or less, found that the visual prognosis of young people with CRVO is often poor. In contrast to all those studies, in my study [ 180 ], none of those under the age of 45 years, with initial visual acuity of 20/60 or better, had visual acuity deterioration, and in those with initial visual acuity of 20/70 or worse, it improved in 80 %.…”
Section: Effect Of Agementioning
confidence: 98%